"You Know the Pyrenees by Day - Come See Them by Night..." Reflections on in visu Artialisation of Nocturnal Skyscapes in the Pyrenees - Bruno Charlier (Revue de Géographie Alpine)
"Nocturnal skyscapes. You know the Pyrenees by day - come see them by night... ": thus the title of an exhibition of photographs set up in 2012 by the Pays de Lourdes et des Vallées des Gaves (Hautes-Pyrénées département) to help raise public awareness about the project for the Pic du Midi International Dark Sky Reserve (IDSR), mainly among the local population and stakeholders in the areas concerned.Although its evocative title might suggest otherwise, this is rather more than an exhibition on the iconic sites of the Pyrenees seen at night. What it seems to do is to bring out new landscapes that are not just "mountainscapes at night", or simply night-time versions of landscapes seen by day.The night skies that characterise these landscapes therefore represent an new category, they need to be considered in their entirety as conveying a meaning that encompasses all that is both construed and material in our relationships with landscape. As in many areas with similar projects either in place (North America, Europe) or emerging (the Cévennes and Mercantour national parks in France, for example), the creation of the Pic du Midi IDSR will have helped to bring a new kind of "landscape object" (Besse, 2009) into being in the Pyrenean region.